2013
DOI: 10.1111/1469-0691.12252
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections with hepatitis B and C viruses in human immunodeficiency virus-infected patients in Morocco

Abstract: Human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) are major public health concerns. We aimed to determine the prevalence of HBV and HCV infections among HIV-infected patients, and to identify the main circulating hepatitis strains in Morocco. The study was carried out in 503 HIV-infected patients. Our survey indicated that the prevalence of HIV/hepatitis co-infection was 10.6%; 5.2% of patients were HBV surface antigen positive, and 5.4% of patients were anti-HCV positive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…The mean age of anti-HIV-positive was 31.7±18.4 years in females and 35.6±20.9 years in males. These results are in agreement with those reported in Egypt and Morocco [29] , [30] .…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of anti-HIV-positive was 31.7±18.4 years in females and 35.6±20.9 years in males. These results are in agreement with those reported in Egypt and Morocco [29] , [30] .…”
Section: Discussionsupporting
confidence: 93%
“…The sustained presence of SGT D7 in the Maghreb was linked to intra-familial transmission in early childhood [ 91 ]. The dominance of SGT D7 in the Maghreb was previously reported by several original and review papers and is consistent with the results of this study [ 49 , 91 , 92 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 94%
“…For those with a history of STD, HCV prevalence was 3%, while for those who tested positive for HIV, HCV prevalence was 20% [ 39 ]. Another study of HIV infected patients reported an HCV prevalence of 5% [ 43 ]. Among hospital attendees, an early study reported HCV prevalence of 10% among inpatients and 6% among outpatients [ 42 ].…”
Section: Resultsmentioning
confidence: 99%